Structure-guided design of immunomodulatory RNAs specifically targeting the cytoplasmic viral RNA sensor RIG-I - Yong, Hui Yee (2021)
The cytoplasmic immune sensor RIG-I detects viral RNA and initiates an antiviral immune response upon activation. It has become a potential target for vaccination and immunotherapies. To develop the smallest but potent immunomodulatory RNA (immRNAs) species, we performed structure-guided RNA design and used biochemical, structural, and cell-based methods to select and characterize the immRNAs. We demonstrated that inserting guanosine at position 9 to the 10mer RNA hairpin (3p10LG9) activates RIG-I more robustly than the parental RNA. 3p10LG9 interacts strongly with the RIG-I helicase-CTD RNA sensing module and disrupts the auto-inhibitory interaction between the HEL2i and CARDs domains. We further showed that 3p10LA9 has a stronger cellular activity than 3p10LG9. Collectively, purine insertion at position 9 of the immRNA species triggered more robust activation of RIG-1.